2018
DOI: 10.1021/acs.langmuir.8b03350
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Soft Colloidal Nanoparticles Interaction in Shear Flow

Abstract: The mechanical behavior of nanoparticle assemblies depends on complex particle interactions that are difficult to study experimentally. Depending on the nanoparticle morphology, these interactions could lead to adhesive and elastic−plastic behavior during contact deformation. The aim of this research is to study the effect of contact interactions between polymer nanoparticles and their impact on the macroscopic properties of formed aggregates. For this purpose, the discrete element method (DEM) was used to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In the past decades, DEM gained popularity, especially in modeling the dynamics of granular media, and also can be used for the modeling of particulate dispersions subjected to flow, allowing significantly higher number of simulated particles than SD because of the consideration of only pairwise interparticle interactions. In our previous works, we demonstrated that the DEM approach represents versatile and robust tool for the prediction of suspension coagulation dynamics and rheology in a good agreement with both theoretical expectations and experimental data. Based on this knowledge, the present study serves as a proof-of-concept for CFD–DEM modeling of viscoelastic behavior of a particle suspension subjected to the oscillatory shear. The results of the model predictions characterize (i) effects of oscillatory shear on a suspending Newtonian fluid, and (ii) dependency of the suspension storage and loss moduli on various systems parameters.…”
Section: Introductionsupporting
confidence: 67%
“…In the past decades, DEM gained popularity, especially in modeling the dynamics of granular media, and also can be used for the modeling of particulate dispersions subjected to flow, allowing significantly higher number of simulated particles than SD because of the consideration of only pairwise interparticle interactions. In our previous works, we demonstrated that the DEM approach represents versatile and robust tool for the prediction of suspension coagulation dynamics and rheology in a good agreement with both theoretical expectations and experimental data. Based on this knowledge, the present study serves as a proof-of-concept for CFD–DEM modeling of viscoelastic behavior of a particle suspension subjected to the oscillatory shear. The results of the model predictions characterize (i) effects of oscillatory shear on a suspending Newtonian fluid, and (ii) dependency of the suspension storage and loss moduli on various systems parameters.…”
Section: Introductionsupporting
confidence: 67%
“…In general, in addition to providing high shear rates, such systems allow better control of process variables such as temperature, flow rates, residence times, and reagents ratios [79][80][81]. From the mechanistic viewpoint, recent studies have provided additional evidence that correlated the success of these synthesis devices with the control of advection, nucleation, and growth processes [64,82,83]. This high level of control over such phenomena has been thought to directly impact the nucleation and subsequent growth of the nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely due to the narrower channels and the abrupt direction changes observed for the reaction mixture in this case. Different levels of shear rate have been reported to strongly impact the NPs' nucleation and growth processes [64,65]. Figure 6 shows the shear rates for each micromixer.…”
Section: Microfluidic Cfd Simulationmentioning
confidence: 99%
“…Moreover, in previous articles, we have found a direct relation between interparticle adhesion and the size of formed nanoparticle aggregates. 15,27,30 Using the previously described numerical tools, the relationship for the adhesive force between nanoparticles and the size of the formed fractal aggregates will be investigated under various shear flow conditions. Particularly, three hypotheses will be studied in order to understand the evolution of aggregate size with the shear rate at temperatures above the polymer shell T g .…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The main considerations taken into account by Marshall are to include the particle concentration field and the body force exerted by the particles into the flow field calculation. This approach has been used in several of our previous articles. , The resulting velocities calculated from the modified N–S equations are then used as an input to calculate the forces affecting each particle. The most relevant forces affecting nanoparticles dispersed in fluids are drag, buoyancy, gravity, van der Waals attraction, electrostatic repulsion, and the force arising from physical NP contact.…”
Section: Methodsmentioning
confidence: 99%